A Study on Correggio Wall Paintings: Characterization of Technique and Materials of Abbey Church of S. Giovanni Evangelista in Parma, Italy - Antonella Casoli; Pier Paolo Lottici; Danilo Bersani (Applied Sciences, 2022)
This study deals with the materials of the sub-arch painting of the Del Bono Chapel of the Abbey Church of S. Giovanni Evangelista in Parma, Italy, datable to around 1523. The artist is Antonio Allegri, known as Correggio (1489–1534), who is considered to be one of the greatest painters of the 16th century. Micro-Raman spectroscopy, micro-Fourier transform infrared spectroscopy and gas chromatography coupled with mass spectrometry were used as the main techniques to identify the pigments and binding media. The analysis enabled us to identify the pigments which were characteristic of the epoch. Correggio’s palette was composed by mineral pigments—sometimes expensive ones such as lapis lazuli, azurite and cinnabar—together with a wide range of earths, or by synthetic pigments like smalt blue. From the amino acid content determination, it was shown that, in the samples containing lazurite, smalt, hematite, green earth and goethite, the protein fraction was attributable to the presence of a mixture of egg and animal glue, from which the use of the a secco technique could be assumed, with pigments that did not need organic binding media on the wall. For the gilding sample, the study found that Au foil had been applied on a brown background (oil-based missione).